Telocytes and Their Structural Relationships With the Sperm Storage Tube and Surrounding Cell Types in the Utero-Vaginal Junction of the Chicken - Zhu, Xudong; Wang, Qi; Pawlicki, Piotr; Wang, Ziyu; Pawlicka, Bernadetta; Meng, Xiangfei; Feng, Yongchao; Yang, Ping (Frontiers in Veterinary Science, 2022)
Telocytes (TCs) are a new type of mesenchymal cells that have been discovered recently in many organs and tissues. However, studies of TCs in the avian reproductive system are still at the beginning. Chickens are one of the world's most popular domesticated animals, providing inexpensive but valuable proteins and nutrients from chickens and eggs to nourish the human bodies. Chickens have important scientific value; thus, understanding the reproductive system regulations seems to be important. The utero-vaginal junction is involved in the regulation of sperm storage. The sperm storage tube (SST) in the utero-vaginal junction stores sperm. The purpose of this study was to investigate the existence of TCs in the utero-vaginal junction of the chicken, and their structural relationships with the sperm storage tube and surrounding cell types. We studied the morphology, ultrastructure, and immune characterization of TCs. Methods The utero-vaginal junction of 4-month-old healthy adult chickens (n = 10) were used for Masson's staining, fluorescent in situ hybridization technique (FISH), and transmission electron microscopy (TEM) analysis. The results showed that TCs were present in the utero-vaginal junction. TCs appear as CD34 immunopositive and C-kit immunopositive. They were identified especially via small-body and long-protrusion telopodes (Tps) containing Podomers (Pm) and Podoms (Pd). The Tps were bent, folded, and intertwined with each other, sometimes in the shape of a labyrinth. The Tps were embedded between collagen fiber bundles, smooth muscle bundles, and around blood vessels and releasing vesicles. TCs surround these glands, forming heteromorphic cell connections with surrounding lymphocytes and plasma cells, smooth muscle cells, blood vessels, collagen fibers, and fibroblast-formed homotypic or allotypic connections in a complex three-dimensional network structure. This study provides a morphological basis for the possible role of TCs in regulating the utero-vaginal junction physiological role and in intercellular communication.